Analisis Penyusunan Laporan Keuangan Berdasarkan SAK EMKM Pada Usaha Kedai Oblong Di Kecamatan Telanaipura (International Forum of Researchers and Lecturers, 2024)
UMKM make a significant contribution to Indonesia's economic growth. IAI released the rules for making financial reports for UMKM after realizing the important role played by UMKM. The purpose of this study is to examine how the Kedai Oblong company, one of the micro, small and medium enterprises in Jambi City, prepares its financial reports in accordance with the Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM). Descriptive techniques are used in the qualitative methodology of this study. This is done by examining the financial records of Kedai Oblong and applying the financial reports according to SAK EMKM. The findings of this study indicate that the financial statements of Kedai Oblong have influenced the financial statements of other companies, it's just that the reports they made have not been prepared according to the EMKM financial standards that have been in effect since January 1 2018, the application of EMKM SAK in presenting income statements has a lower difference than the calculation report made by the oblong shop. The author uses SAK EMKM in the results and discussion to prepare the presentation of financial reports at the Oblong Shop in accordance with the applicable SAK EMKM standards and rules.